Can we use molecular dynamics to simulate biomolecular recognition? - Lüking, Malin; van der Spoel, David; Elf, Johan; Tribello, Gareth A. (Uppsala University, 2023)
This Dataset contains starting structures, inout files and scripts to prepare and run normal and biased simulations on the LacI Transcriptionfactor and DNA (with different sequences). The starting structures (based on the crystal structure with PDB ID 1EFA), input files for GROMACS and PLUMED and scripts for prepartion and analysis are also available on GitHub. In this dataset, one can additionally find the trajetories of the simulations that were run to produce the linked publication.

The trajectories include the follwing sets:

Unbiased simulations

5 replica of 50 ns each

NMR restraint simulations

2 DNA sequences: specific, OSymL and non-specific NOD

3 replica of 250 ns each

Metadynamics simulations

OSymL (specific DNA sequence)

bias on selected contacts between the protein and the DNA

bias on selected contacts between the protein and the DNA and between the two hinge helices

bias on selected contacts between the protein and the DNA and between the two hinge helices and the hinge helixity

NOD (non-specific DNA sequence)

bias on selected contacts between the protein and the DNA and between the two hinge helices and the hinge helixity

Code contains the scripts used for preparing, running and analysing the simulations. It is also available on GitHub (https://github.com/mallu2/Transcriptionfactor_unbinding) (https://github.com/mallu2/Transcriptionfactor_unbinding) .
Keywords: Bioinformatics and computational biology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)